AGRARIAN ADVOCATION SYSTEM (MODEL UPAYA RESOLUSI KONFLIK AGRARIA PADA MASYARAKAT DI DESA WARU BARAT) - guyani, gugun (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2021)
Land conflicts have always been an arena for classical discourse and have always been attractive, especially in the midst of the weak awareness and structure of the State and society which are still low and not well managed. The community's ignorance of the procedures for land registration services actually triggers the potential for increased land conflicts or disputes among the people involved in the conflict. The purpose of this research is to find out 1) what is the role of the village head in ensuring legal certainty over land ownership rights in the community in West Waru village, 2) what is the form of community participation in ensuring legal certainty over the land of residents in West Waru Village, 3) -factors influencing community participation to guarantee and protect legal rights for land voters. This descriptive research is expected to produce descriptive data in the form of written words, oral people or even certain behaviors and symptoms through observation techniques, in-depth interviews, and documentation. Meanwhile, to test the validity of the data the researcher used the source triangulation technique by comparing the data from the interview results with the contents of the document. The results of this study show that first, the roles of the village head can be carried out through a) The role of legislation, namely the preparation of various statutory instruments for legal certainty. b) The role of administrative services, especially those concerning the aspect of land registration, so that it can be implemented with simple procedures and low cost. Second, the success of implementing village community autonomy cannot be separated from the active participation of community members both from the policy formulation and policy application stages. Among the factors that affect the level of community participation in the village of West Waru are internal factors and external factors, internal factors include 1) Consciousness or Willingness, 2) Educational Factors, 3) Income or Income Factors. External factors which include 1) Government Leadership, 2) Equipment / Facilities